Perceived Risk Modifies the Effect of HIV Knowledge on Sexual Risk Behaviors - Noroozinejad, Gholamhossein; Yarmohamadi, Mosaieb; Bazrafkan, Fatemeh; Sehat, Mahmoud; Rezazadeh, Majid; Ahmadi, Khodabakhsh (Frontiers in Public Health, 2013)
Background There is a large controversy in the literature about the inter-relations between perceived risk, knowledge and risk behavior in different settings, and people at HIV risk are not an exception. Aim To assess additive and multiplicative effect of perceived HIV risk and HIV knowledge on sexual risk behavior of Injecting Drug Users (IDUs). Method We enrolled 162 street based IDUs to this analysis. Data came from a national survey of IDUs in Iran, with a cross sectional design. Socio-demographics (employment, education, marital status), HIV knowledge, perceived HIV risk and four different sexual risk behavior were registered. In the first step, using spearman test, the association of HIV knowledge and risk behavior were tested, then possible moderating effect of perceived HIV risk on this association was determined. Results Although among IDUs with low perceived HIV risk, HIV knowledge was negatively associated with sexual risk behavior (P<0.05 for all), this association was not significant among IDUs with high perceived HIV risk (P>0.05 for all). Thus perceived HIV risk moderated the association between HIV knowledge and sexual risk behavior. Conclusion Perceived risk should be taken into consideration when studying the effect of HIV knowledge on sexual risk behavior of IDUs. Findings may help us better understand negative effects of fear arousing interventions as a part of HIV prevention media campaigns.